Study of the joint action of coenzyme Q10 and royal jelly on the hematological and spirometric indicators in the elite athletes - S. V. Kopylova; A. N. Ovchinnikov; M. A. Shabalin; A. V. Deryugina; V. N. Krylov; V. G. Kuzmin; D. I. Voronin; O. V. Shabalina (Спортивная медицина: наука и практика)
Objective: to study the effects of royal jelly and coenzyme Q10 administered with food on the number of hematological and spirometric indicators in elite swimmers in precompetitive period. Materials and methods: 16 highly qualified athletes at the age of 19,8±0,6 years participated in the study. Content of erythrocytes and different white blood cells and level of hemoglobin in the blood of the athletes were measured using hematology analyzer «Abacus Junior 30». The measurement of respiratory volume, respiratory minute volume, respiratory frequency, рO2 and рCO2 in expired air, alveolar рO2 and рCO2 in the subjects was made using anesthesia breathing apparatus «Capnomac Ultima». Results: the administration of the above mix by the athletes stimulates the immune system and the oxygen-transporting function of blood, activates the functional state of pulmonary tissue, increases the oxygen consumption and improves physical performance. Conclusions: the effect of preventive therapy on the analyzed parameters in highly qualified swimmers determine the feasibility of the competent intake of composition «royal jelly-ubiquinone-10-honey» before and during major competitions when the requirements are high.